IMF Research Bulletin, December 2011. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2011)
The Q and A in this issue features seven questions about Large Fiscal Consolidation Attempts in the Past and Implications for Policymakers Today (by Fuad Hasanov and Paolo Mauro). The research summaries are "Booms and Busts" (by Roberto Piazza) and " Did Export Diversification Soften the Impact of the Global Financial Crisis?" (by Rafael Romeu). The issue also provides details on visiting scholars at the IMF (mainly from September through December 2011), as well as recently published IMF Working Papers and Staff Discussion Notes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet